Answer:
- A(1) = -4
- A(n) = A(n - 1) - 6
Step-by-step explanation:
Given
- AP with the explicit formula A(n) = 8 - 6(n - 1)
To find
Solution
Recursive formula is the formula A(n) = A(n - 1) + d
Based on the explicit formula we have:
- A(n) = 8 - 6(n - 1) = 8 - 6n + 6 = 2 - 6n
- A(n - 1) = 2 - 6( n - 1) = 2 - 6n + 6 = 8 - 6n
The common difference is:
- d = A(n) - A(n - 1) = 2 - 6n - (8 - 6n) = 2 - 6n - 8 + 6n = - 6
The first term is:
- A(1) = 2 - 6(1) = 2 - 6 = -4
So the recursive formula is:
- A(1) = -4
- A(n) = A(n - 1) - 6